2019
DOI: 10.1002/ppap.201900072
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the anticancer effects induced by cold atmospheric plasma in 2D and 3D cell‐culture models

Abstract: The biological characteristics of three‐dimensional (3D) tumors cannot be adequately represented through two‐dimensional (2D) cell cultures. Here, to acquire more precise information about plasma–tumor interactions, the plasma‐induced cytotoxicity was tested in both 2D cell culture and 3D tumor‐spheroid culture. The results indicated that the toxic effects were markedly reduced in 3D cancer cells compared with 2D cells. We found that reactive oxygen and nitrogen species can penetrate through the entire depth o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
17
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 66 publications
(106 reference statements)
1
17
1
Order By: Relevance
“…It was reported that despite the ability of RONS to penetrate throughout the entire depth of 3D tumourspheroids, apoptosis was observed only on the outermost layer or surface. [9] However, this is not what occurs in our case. We used confocal microscopy alongside a 3D reconstruction of stacked images to build three-dimensional maps of the treated tumourspheres.…”
Section: Pin-to-plate Discharge Presents Cytotoxicity Toward Gbm Cell...contrasting
confidence: 79%
See 2 more Smart Citations
“…It was reported that despite the ability of RONS to penetrate throughout the entire depth of 3D tumourspheroids, apoptosis was observed only on the outermost layer or surface. [9] However, this is not what occurs in our case. We used confocal microscopy alongside a 3D reconstruction of stacked images to build three-dimensional maps of the treated tumourspheres.…”
Section: Pin-to-plate Discharge Presents Cytotoxicity Toward Gbm Cell...contrasting
confidence: 79%
“…[5,6] Devices that generate CAP can be divided into: direct-discharge (i.e., dielectric barrier discharge (DBD), pin to plate system) and indirect-discharge (i.e., plasma jets, pens, and torches). [5,7] CAP-induced cancer cellular cytotoxicity has been demonstrated previously by using different devices, such as plasma jet, [8][9][10][11][12] micro-sized devices, [13] DBDs [14,15], and corona discharges. Previous studies have reported both direct and indirect CAP treatment efficacies in inducing anticancer effects (in numerous cancer types, such as pancreatic, [8] lung, [9,10] squamous cell carcinoma, [11] brain, [13] and so forth) in in vitro [8,9,11] and antitumor effects in vivo.…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…The contents of aqueous O 2 − /ONOO − /ONOOH were measured using the TEMPONE-H (1-hydroxy-2,2,6,6-tetramethyl-4-oxo-piper-idine, Enzo, 5 mM). Detailed ROS and RNS detection methods are outlined in our previous paper [ 45 ]. PAS sampling for H 2 O 2 , NO 2 − and NO 3 − measurement were completed within 5 min after plasma irradiation due to other operations.…”
Section: Methodsmentioning
confidence: 99%
“…In this paper, based on three-dimensional (3D) T24 bladder tumour spheroids (which more accurately mimic the biological characteristics of cancer cells in vivo than other models), [14,15] the anticancer effects of a helium atmospheric pressure plasma jet combined with four commonly used clinical antibladder cancer drugs (cisplatin, methotrexate, adriamycin and paclitaxel) were tested. The effects of these four drugs on the global ROS levels in the medium of the plasma jet-treated spheroids were analysed by detecting the oxidation-reduction potential (ORP).…”
mentioning
confidence: 99%